Pemberdayaan Petani Hortikultura (Kasus Kelompok Tani Werdhi Guna Desa Pempatan, Kecamatan Rendang, Kabupaten Karangasem) - JUNIARTA, I KOMANG; SARJANA, I MADE; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Empowerment of Horticultural Farmers: The Case of Werdhi Guna Farmer Group of Pempatan Village, Rendang District, Karangasem Regency Pempatan Village, Rendang District, Karangasem Regency has great vegetable potential, but farmers have not been able to utilize the condition well. There needs to be empowerment to increase farmer's income and farmer's prosperity. The purpose of this research is to know (1) horticultural potential (2) process of empowering horticulture farmers. This research used qualitative and quantitative analysis methods. The results showed the potential of vegetable horticulture (Olericulture) in Werdhi Guna Farmer Group with the achievement of score 4.2 with the good category meaning that Werdhi Guna Farmer Group has a tropical area and is suitable for horticultural cultivation. Horticultural plants grow with maximum results, seen from the fact that vegetable crops are fertile although obstacles still persist such as the limited availability of water for watering plants. As for the empowerment of farmers, it is of good category with average achievement score of 3.9 meaning that the farmers play an important role in horticultural cultivation and the importance of government roles given to Werdhi Guna Farmer Group in enhancing knowledge or innovation in agriculture. In this research, it is suggested that farmers in Werdhi Guna Farmer Group are expected to be able to increase their horticultural products in order to be able to compete in the market to improve farmer's welfare, and of course to promote vegetable farming (Olericulture) and the government should pay more attention to horticultural farmers and provide support in the form of aid and training that can make them able to increase their farming.